Preparation method of nickel-based catalyst and application of nickel-based catalyst in hydrogen production through ammonia decomposition
By constructing the atomically dispersed Ni-O-Ce structure, the problems of low catalytic activity and complex preparation of nickel-based catalysts are solved, and high-efficiency ammonia decomposition catalysis at low temperatures are achieved, which enhances stability and cycleability, and simplifies the The preparation process and reduces costs.
Patent Information
- Application Number
- CN202411297437.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The existing nickel-based catalysts have low catalytic activity at low temperatures, and the preparation process is complex and time-consuming, resulting in limited industrial applications. The agglomeration of nickel nanoparticles affects activity and stability.
A simple and efficient synthetic method is used to prepare Ni/CeOx catalyst, and dissolve it by stirring and dissolving the nickel precursor and Ce precursor in ultrapure water, adding sodium hydroxide and sodium carbonate to form a mixed alkali solution, and crystallization is carried out by dropping funnel method and Reduction treatment constructs atomically dispersed Ni-O-Ce structure to inhibit the agglomeration of nickel nanoparticles.
The complete conversion of ammonia decomposition is achieved under low temperature conditions (<500℃), which significantly improves catalytic activity and stability, reduces energy consumption, simplifies the preparation process, reduces production costs, and has industrial potential.
Smart Images

Figure CN119158583A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation and heterogeneous catalysis, and more specifically, to a method for preparing a nickel-based catalyst and application thereof in hydrogen production by decomposing ammonia. Background Art
[0002] As society continues to progress, the hydrogen economy is becoming more prosperous. Hydrogen is large in volume and difficult to liquefy, so its storage and transportation are a major problem. ΔH=91.2kJ mol -1 ) releases hydrogen and nitrogen, which is environmentally friendly and pollution-free. Ammonia provides a clean molecular storage medium for hydrogen, making this reaction a research hotspot in recent years. The large-scale application of ammonia as a hydrogen carrier has the following bottlenecks. First, there is the problem of the decomposition temperature of ammonia. The decomposition of ammonia is an endothermic reaction, which requires high temperature to achieve its complete conversion, and because it is an endothermic reaction, a large amount of energy input is required to maintain the reaction conditions. Secondly, the toxicity of ammonia is a basic safety issue during operation. Therefore, it can be seen that the key countermeasure for the large-scale use of NH3 as a hydrogen carrier is to design and construct efficient NH3 decomposition catalysts to reduce the reaction temperature, reduce energy costs, and improve process safety.
[0003] In recent years, a large number of research works have emerged to address this scientific issue, and many catalytic systems have been designed, such as Ru / MgO, Ru / CNTs, Ru / CeO2, Fe / MgO, Co / NC-600, CuZn / Al2O3, etc. Although Ru-based catalysts have excellent catalytic activity for ammonia decomposition, Ru is a precious metal and has a small reserve, which makes the preparation cost of the catalyst high. Other non-precious metals have low activity for ammonia decomposition and require higher temperatures, which invisibly hinders the real industrial application of these catalysts. Nickel-based catalytic systems have excellent catalytic performance for ammonia decomposition, making them a potential powerful alternative to Ru-based catalysts. Therefore, more and more researchers are turning their attention to the research of Ni-based catalysts.
[0004] Nickel-based catalytic systems have been applied to the study of ammonia decomposition reactions, such as Ni / ZrO2, Ni / MgO, Ni / CeO2, Ni / CaNH3, Ni / SiO2, and Ni / Al2O3. However, there are still some problems in many studies. For example, (1) the preparation process of some catalysts is relatively complicated and time-consuming, and the catalysts are not easy to prepare in large quantities, which is not conducive to industrial production; (2) Nickel nanoparticles tend to agglomerate during the reaction, which greatly affects the activity and stability of the catalyst; (3) The catalytic activity of nickel-based catalytic systems for ammonia decomposition at low temperatures (<450°C) is generally low.
[0005] The comparative example 1 of the embodiment design of the specification of patent CN112337494B clearly discloses a Ni / CeO2 ammonia decomposition hydrogen production catalyst, and the Ni / BN-CeO2 catalyst disclosed at the same time has an ammonia conversion rate of more than 99.5% and a hydrogen generation rate of 33.4mmol / (gcat·min), but the nickel-based catalytic system needs to be decomposed into hydrogen for ammonia in an NH3 atmosphere at 500-750°C. Patent CN117065765A discloses an ammonia decomposition hydrogen production catalyst and its preparation method and application. The Ni / BN-CeO2 ammonia decomposition hydrogen production catalyst prepared in Example 1 has a conversion efficiency of 99.6%, and needs to be decomposed into hydrogen for ammonia in an NH3 atmosphere at 650°C. CN115646500B provides an ammonia decomposition hydrogen production catalyst, and Example 3 clearly prepares a catalyst containing nickel and cerium, and pre-reduced in a 50% H2 / N2 atmosphere (120mL / min) at 700°C for 1h. After the reduction was completed, the reaction temperature was lowered to 550°C under a 50% H2 / N2 atmosphere. After the temperature dropped to 550°C, NH3 (molar ratio 1:1, GHSV = 6000 mL / g) was switched to cat h) to carry out ammonia decomposition reaction. The journal article (Nano Research, Volume 11, pages 4412–4422, (2018)) discloses a simple synthesis of graphene-supported Ni-CeOx nanocomposite materials as an efficient catalyst for borane ammonia hydrolysis dehydrogenation. The nickel nanocatalyst doped with CeOx and supported on graphene (Ni-CeOx / graphene) was synthesized through a simple chemical reduction route and used as a powerful catalyst for AB hydrolysis in aqueous solution at room temperature. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention innovatively adopts a simple and efficient synthesis method to prepare an atomically dispersed catalyst, which can achieve complete ammonia decomposition under low temperature conditions (<500°C) and exhibits excellent catalytic performance in the ammonia decomposition hydrogen production reaction.
[0007] To achieve the above object, the technical solution of the present invention is as follows:
[0008] In one aspect, the present invention provides a nickel-based catalyst, wherein the nickel-based catalyst is Ni / CeO x Catalytic system (in this application, represented by Ni / CeO x (H450)), where 1≤x<2.
[0009] Furthermore, the catalytic system constructs an atomic-level dispersed structure of Ni-O-Ce.
[0010] In another aspect, the present invention provides a method for preparing a nickel-based catalyst, the specific steps of which are as follows:
[0011] S1: dispersing a nickel precursor and a Ce precursor in ultrapure water, and stirring and dissolving them to obtain a nickel-cerium mixed salt solution A;
[0012] S2: dissolving sodium hydroxide and sodium carbonate in ultrapure water, and stirring to dissolve to form a mixed alkaline solution B;
[0013] S3: After the deionized water is heated, solution A and solution B are added simultaneously using a dropping funnel, stirred, crystallized, washed and precipitated by centrifugation, dried and ground into powder to obtain a catalyst precursor;
[0014] S4: reducing the catalyst precursor under a hydrogen atmosphere to obtain a nickel-based catalyst.
[0015] Furthermore, the nickel precursor is selected from soluble nickel salts such as nickel nitrate hexahydrate (Ni(NO3)2·6H2O), nickel chloride hexahydrate (NiCl2·6H2O), and nickel sulfate hexahydrate (NiSO4·6H2O).
[0016] Furthermore, the cerium precursor is selected from soluble cerium salts such as cerium nitrate hexahydrate (Ce(NO3)3·6H2O), cerium sulfate tetrahydrate (Ce(SO4)4·4H2O), and cerium ammonium nitrate ((NH4)2Ce(NO3)6).
[0017] Furthermore, the molar ratio of nickel to cerium in the nickel precursor and the Ce precursor is 0.5 to 4. The change in the molar ratio of nickel to cerium in the nickel precursor and the Ce precursor will affect the number of interfaces between Ni and Ce. If the molar ratio is too low, the number of interfaces is too small, the electronic regulation effect on Ni will be weakened, and the improvement of activity will be weakened. Moreover, Ni is an active metal, and the loading is too low, and the activity will be relatively poor. If the molar ratio of nickel to cerium in the nickel precursor and the Ce precursor is too high, the content of Ni is too much, and the content of Ce is too little, the interaction between Ni and Ce will be weakened, the particle size of Ni will be too large during the reaction, and it is easy to agglomerate, the stability will be destroyed, and it will be difficult to operate stably for a long time.
[0018] Furthermore, in S1 and S2, the amount of ultrapure water is 50-100 mL. The appropriate amount of ultrapure water is to ensure that the solution has a certain ion concentration and can form a uniform catalyst precursor. If the amount of water is too little, the ion concentration is too high, the sedimentation rate is too fast, the crystallized grain size is too large, and the amount of ultrapure water is too much, which will cause the subsequent filtration and washing process to be too troublesome.
[0019] Furthermore, the molar amount of the sodium hydroxide is 0.5 to 3 times the sum of the molar amounts of the nickel precursor and the Ce precursor. The molar amount of sodium hydroxide is used to ensure that the pH of the solution is within a suitable range, to ensure that the ions in the solution can precipitate and crystallize, and not to increase the catalyst preparation cost due to the large amount of sodium hydroxide used.
[0020] Furthermore, the molar amount of the sodium carbonate is 1 to 4 times the sum of the molar amounts of the nickel precursor and the Ce precursor. Preferably, the sodium carbonate is anhydrous sodium carbonate. The molar amount of sodium carbonate is to ensure atomic dispersion between Ni and Ce. The catalyst preparation method is based on the preparation method of hydrotalcite. 2- Will enter the intercalation layer to balance the charge.
[0021] Furthermore, the crystallization temperature is 60 to 120°C, preferably 70 to 100°C. Furthermore, the crystallization time is 1 to 6 hours, preferably 3 hours. If the crystallization temperature is too high, the grains will become larger. If the crystallization temperature is too low, the grain reconstruction will be difficult and uniform grains cannot be formed. The longer the crystallization time, the more uniform the formed grains. However, if the crystallization time exceeds the preferred time of this application, the catalyst preparation will be too time-consuming. If the crystallization time is too short, it will be difficult to complete the crystallization process.
[0022] Furthermore, in S3, the deionized water needs to be heated to 70-100°C, preferably 80°C.
[0023] Furthermore, in S3, solution A and solution B are added at the same time using a dropping funnel, stirred at 80°C for 2h, and after being evenly mixed, maintained at 80°C for crystallization. The purpose of adding solution A and solution B dropwise is to control the rapid increase in the concentration of ions in the solution and to control the sedimentation rate. If solution A and solution B are directly mixed and then heated, uneven sedimentation will result. Stirring is required during the catalyst preparation process to ensure uniform distribution of ions in the solution.
[0024] Furthermore, the reduction temperature is 400-600°C, preferably 450°C, and the time is 1-4h, preferably 2h. The reduction time can be determined according to the filling amount of the catalyst. If the reduction time is too short, the catalyst cannot be completely reduced; if the reduction temperature is too low, the activity of the nickel-based catalyst will be weakened; if the reduction time is too long, the particle size of Ni will increase, and the pretreatment process will be too long.
[0025] On the other hand, the present invention provides an application of the nickel-based catalyst of the present invention in the field of ammonia decomposition hydrogen production reaction.
[0026] Beneficial effects:
[0027] The present invention constructs Ni / CeO x Catalytic system, the value of X ranges from 1 to 2. During the catalyst preparation process, a large number of Ni-O-Ce interfaces are constructed, and a large amount of oxygen is removed during the reduction process to form oxygen vacancies (such as Figure 2 Based on Ni / CeO x Atomic dispersion characteristics of the catalytic system, Ni and CeO xThe close contact between them forms a strong metal-carrier interaction, that is, by constructing an atomic-level dispersed structure of Ni-O-Ce to enhance the interaction between the metal carriers. During the reduction process, a large amount of Ni-O V -Ce structure, regulating the electronic state of Ni, achieving the purpose of inhibiting the agglomeration of nickel nanoparticles while improving its catalytic activity at low temperatures, enhancing the stability and cyclability of the catalytic system, and having certain industrialization potential.
[0028] Traditional Ni-based catalysts (such as the catalysts in the literature mentioned in the background technology) need to achieve complete conversion at 650-700°C. The Ni / CeO x The catalytic system can achieve complete conversion at 550°C and maintain stable operation. It passed the cyclic test 5 times and there was no performance degradation during the cycle.
[0029] The Ni / CeO x The catalytic system can be used in ammonia gas at 10 mL min -1 At a flow rate of 500℃, ammonia can be almost completely converted into hydrogen. At 550℃, the conversion rate has exceeded the equilibrium conversion rate. Even if the flow rate is increased to 3 times, the performance does not decrease, and complete conversion can be achieved. In this way, the hydrogen production rate can be increased without increasing the temperature, and efficient hydrogen production can be achieved at low temperatures. Compared with traditional Ni-based catalysts, the temperature drops by more than 100 degrees during complete conversion, which greatly reduces the material requirements for hydrogen production equipment. In addition, when the temperature is reduced, the energy consumption will be greatly reduced, which is conducive to saving energy consumption. At the same time, the catalyst preparation method is simple, easy to repeat, low in production cost, and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The catalyst sample is Ni / CeO x Activity evaluation of (H450) and control samples Ni / CeO2-IM, Ni / Al2O3
[0031] Figure 2 The catalyst sample is Ni / CeO x (H450) Enlarged test image
[0032] Figure 3 The catalyst sample is Ni / CeO x (H450) cyclability evaluation curve
[0033] Figure 4 The catalyst sample is Ni / CeO x Stability evaluation of (H450)
[0034] The present invention will be further described below in conjunction with specific examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with specific examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0036] Example 1 Ni / CeO x Preparation of (H450)
[0037] (1) 0.1 mol of nickel precursor Ni(NO3)2·6H2O and 0.05 mol of Ce precursor Ce(NO3)3·6H2O were added to 50 mL of ultrapure water and stirred for 20 min to form a uniform nickel-cerium mixed salt solution A;
[0038] (2) Add 0.3 mol of Na2CO3 and NaOH to 50 mL of ultrapure water and stir for 20 min to form a uniform mixed alkaline solution B;
[0039] (3) Add 10 mL of deionized water to a beaker and heat to 80°C. Then, use a dropping funnel to add solutions A and B to the beaker at the same time and stir at 80°C for 2 h.
[0040] (4) Then stop stirring, crystallize at 80° C. for 3 h, wash the precipitate with deionized water by centrifugation, wash repeatedly by centrifugation until the supernatant is neutral, and then dry at 90° C. for 12 h; after it is fully dried, grind it into powder to obtain a catalyst precursor;
[0041] (5) The precursor was reduced and treated at 450°C in a hydrogen atmosphere for 2 h at a heating rate of 5°C / min to obtain the catalyst system of the present invention, represented by: Ni / CeO x (H450).
[0042] Example 2
[0043] The difference from Example 1 is that the nickel precursor is replaced by NiCl2·6H2O, the nickel-cerium precursor is at a molar ratio of 0.5, the amount of ultrapure water is 100 mL, and the amount of anhydrous sodium carbonate is 4 times the sum of the molar amounts of the nickel-cerium precursors; the crystallization temperature is 100°C, the crystallization time is 6 h, the hydrogen reduction temperature is 400°C, and the time is 4 h.
[0044] Example 3
[0045] The difference from Example 1 is that the nickel precursor is replaced by NiSO4·6H2O, the nickel-cerium precursor is in a molar ratio of 4, the amount of ultrapure water is 100 mL, the amount of sodium hydroxide is 0.5 times the sum of the molar amounts of the nickel-cerium precursors, and the amount of anhydrous sodium carbonate is 1 times the sum of the molar amounts of the nickel-cerium precursors; the crystallization temperature is 70°C, the crystallization time is 1 h, the hydrogen reduction temperature is 600°C, and the time is 2 h.
[0046] Example 4
[0047] The difference from Example 1 is that: the Ce precursor is replaced by Ce(SO4)4·4H2O, the nickel-cerium precursor is in a molar ratio of 1, the amount of sodium hydroxide used is 1 times the sum of the molar amounts of the nickel-cerium precursors, and the amount of anhydrous sodium carbonate used is 4 times the sum of the molar amounts of the nickel-cerium precursors; the crystallization temperature is 90°C, the crystallization time is 2h, the hydrogen reduction temperature is 500°C, and the time is 3h.
[0048] Example 5
[0049] The difference from Example 1 is that: the Ce precursor is replaced by (NH4)2Ce(NO3)6, the nickel-cerium precursor is in a molar ratio of 1, the amount of sodium hydroxide used is 3 times the sum of the molar amounts of the nickel-cerium precursors, and the amount of anhydrous sodium carbonate used is 1 times the sum of the molar amounts of the nickel-cerium precursors; the crystallization temperature is 75°C, the crystallization time is 5h, the hydrogen reduction temperature is 600°C, and the time is 1h.
[0050] Comparative Example 1 Preparation of Control Sample 1
[0051] The difference from Example 1 is that the Ce precursor is replaced by Al(NO3)3·9H2O, expressed as: Ni / Al2O3(H450).
[0052] Comparative Example 2
[0053] Weigh 0.1 mol of commercial CeO2 and disperse it in 50 mL of ultrapure water. Ultrasonic dispersion is performed for 20 min. Weigh 0.1 mol of Ni(NO3)2·6H2O and add it to the above solution. After evaporation at 90 °C, reduce it at 450 °C in a hydrogen atmosphere for 2 h with a heating rate of 5 °C / min to obtain Ni / CeO2-IM.
[0054] Test 1Ni / CeO x Application of catalytic system in ammonia decomposition reaction
[0055] (1) Weigh about 90 mg of the catalyst sample Ni / CeO prepared in Example 1. x The catalyst activity of (H450) and the control samples Ni / CeO2-IM and Ni / Al2O3 were evaluated in the range of 250℃~650℃, with ammonia 10mL min -1flow rate; Figure 1 shown.
[0056] It can be seen from the figure that the catalyst sample Ni / CeO prepared in Example 1 x (H450) showed excellent activity improvement, and its activity was twice as high as that of Ni / Al2O3 at 450°C, indicating that the strategy of improving the activity of catalyst for hydrogen production by ammonia decomposition by regulating the electronic state is feasible. Compared with Ni / CeO2-IM prepared by impregnation method (Comparative Example 2), the catalyst sample Ni / CeO2 prepared in Example 1 has a good x The (H450) activity was increased by more than two times, indicating that the atomic-level dispersed catalyst obtained by this method is superior in the ammonia decomposition hydrogen production reaction. At the same time, compared with the existing catalysts, the traditional Ni-based catalyst needs to be above 700°C to achieve complete conversion. The catalyst sample Ni / CeO prepared in Example 1 x (H450) is almost completely converted at 500℃.
[0057] (2) Weigh about 90 mg of the catalyst sample Ni / CeO prepared in Example 1. x (H450), conduct a catalyst recyclability evaluation experiment. During each cycle, the temperature is raised to 650°C for testing, then lowered to 150°C, and then raised to 650°C for a second test; Figures 2-3 shown.
[0058] from Figure 3 It can be seen that by carrying out a scaled-up test on the catalyst prepared in Example 1, it can be known from the test results that complete conversion is achieved at 500°C, and the conversion rate is as high as 93% at 450°C.
[0059] The catalyst needs to be between 500-550°C to achieve complete conversion. Figure 3 It can be seen that after five cycles of testing from low temperature (250°C) to high temperature (650°C), the activity did not show a significant decrease, indicating that the catalyst prepared in Example 1 has excellent recyclability and has the potential for industrialization.
[0060] It can be seen from the experiment that the catalyst prepared in Example 1 has excellent catalytic activity for ammonia decomposition reaction: ammonia can be almost completely converted at 500°C, and the reaction rate is at the highest level of current nickel-based catalysts; the catalyst prepared in Example 1 has excellent stability and recyclability: after the stability test at 500°C and 65h, the activity of the catalytic system did not show a significant decrease; in addition, after five cycles of heating (250°C)-cooling (650°C), the activity did not show a significant decrease.
[0061] (3) Take about 90 mg of the catalyst sample Ni / CeO prepared in Example 1 x (H450), a catalyst stability evaluation experiment was conducted at 500 °C for 65 h; Figure 4 shown.
[0062] from Figure 4 It can be seen that after the stability test at 500°C for 65h, the activity of the catalytic system prepared in Example 1 did not show a significant decrease, indicating that the catalyst exhibits excellent recyclability and stability, making the catalytic system have the potential for industrialization.
[0063] It can be seen from the test results of Test 1 that the catalytic system prepared in the embodiment of the present application is atomically dispersed, the metal is in close contact with the carrier, and compared with the ordinary impregnation method, the nickel nanoparticles and CeO2 form a strong interaction, which effectively adjusts the geometry and electronic structure of the metal nickel, thereby significantly promoting the rate-determining step in the ammonia decomposition process, and improving its catalytic performance of the ammonia decomposition reaction at low temperatures, so that ammonia can be completely converted at 500°C. The strong interaction formed by the atomic-level dispersion between the nickel nanoparticles and CeO2 can effectively inhibit the agglomeration of the nickel nanoparticles and enhance the stability and cyclicity of the catalytic system.
[0064] In summary, the atomically dispersed catalyst obtained by this method improves the dispersion between Ni and Ce, enhances the interaction between metal carriers, and adjusts the electronic structure of metallic nickel by constructing a Ni-O-Ce interface. A large amount of Ni-O V -Ce interface, increasing the electron density on Ni and promoting the association and desorption of N, achieving the purpose of high activity at low temperature (500°C); by utilizing the metal carrier interaction between Ni and CeO2, the agglomeration of nickel nanoparticles is inhibited, thereby enhancing the stability of the catalytic system, making the catalytic system have certain industrial application potential.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nickel-based catalyst, characterized in that: The specific steps are as follows: S1: dispersing a nickel precursor and a Ce precursor in ultrapure water, and stirring and dissolving them to obtain a nickel-cerium mixed salt solution A; S2: dissolving sodium hydroxide and sodium carbonate in ultrapure water, and stirring to dissolve to form a mixed alkaline solution B; S3: After the deionized water is heated, solution A and solution B are added simultaneously using a dropping funnel, stirred, crystallized, washed and precipitated by centrifugation, dried and ground into powder to obtain a catalyst precursor; S4: reducing the catalyst precursor under a hydrogen atmosphere to obtain a nickel-based catalyst.
2. The preparation method according to claim 1, characterized in that: The nickel precursor is selected from at least one of nickel nitrate hexahydrate, nickel chloride hexahydrate and nickel sulfate hexahydrate.
3. The preparation method according to claim 1, characterized in that: The cerium precursor is selected from at least one of cerium nitrate hexahydrate, cerium sulfate tetrahydrate and cerium ammonium nitrate.
4. The preparation method according to claim 1, characterized in that: The molar ratio of nickel to cerium in the nickel precursor and the cerium precursor is 0.5-4.
5. The preparation method according to claim 1, characterized in that: In S1 and S2, the amount of ultrapure water used is 50-100 mL.
6. The preparation method according to claim 1, characterized in that: The molar amount of the sodium hydroxide is 0.5 to 3 times the sum of the molar amounts of the nickel precursor and the Ce precursor; the molar amount of the sodium carbonate is 1 to 4 times the sum of the molar amounts of the nickel precursor and the Ce precursor.
7. The preparation method according to claim 1, characterized in that: In S3, the deionized water needs to be heated to 70-100°C, and solution A and solution B are added simultaneously using a dropping funnel, stirred at 80°C for 2h, and after being evenly mixed, maintained at 80°C for crystallization; The crystallization temperature is 60-120° C., preferably 70-100° C.; the crystallization time is 1-6 hours, preferably 3 hours.
8. The preparation method according to claim 1, characterized in that: The reduction temperature is 400-600° C., preferably 450° C., and the reduction time is 1-4 hours, preferably 2 hours.
9. A nickel-based catalyst prepared by the method according to any one of claims 1 to 8, characterized in that: The nickel-based catalyst is Ni / CeO x Catalytic system, wherein 1≤x<2; The catalytic system constructs an atomic-level dispersed structure of Ni-O-Ce.
10. Use of the nickel-based catalyst according to claim 9 in the field of hydrogen production by decomposing ammonia.
Citation Information
Patent Citations
A catalyst for hydrogen production from ammonia decomposition, its preparation method and application
CN112337494B
Ammonia decomposition hydrogen production catalyst and its preparation method and application
CN115646500B
Catalyst for hydrogen production through ammonia decomposition as well as preparation method and application of catalyst
CN117065765A
Method of reverse water gas shift reaction for reverse water gas shift catalyst
CN103183346A
Application of metal-loaded catalyst taking rare earth carbonate as carrier precursor in ammonia decomposition reaction
CN111215063A
Cited By
Preparation method of nickel-based catalyst based on expanded graphite dispersion and application of nickel-based catalyst in hydrogen production through ammonia cracking
CN121945084A
Preparation method of nickel-based catalyst based on expanded graphite dispersion and application thereof in hydrogen production by ammonia cracking
CN121945084B
